Minyak Atsiri Temu Putih (Curcuma Zedoaria Rosc., Zingiberaceae) Menurunkan Ekspresi CD4+ Pada Gingiva Terpapar A. Actinomycetemcomitans - Handajani, Juni (Majalah Kedokteran Gigi Indonesia, 2013)
Aggregatibacter actinomycetemcomitans (A. actinomycetemcomitans) is a gram-negative bacteria associated with periodontal disease. Positive expression of CD4+ is shown in gingivitis and periodontitis. The aim of this study was to determine the effect of curcuma zedoaria Rosc., volatile oil against CD4+ expression on gingiva exposed A. actinomycetemcomitans. The study was conducted on male Wistar rats aged 3 months that were exposed bacteria A. Actinomycetemcomitans. Treatment group as many as 5 rats were administered orally with curcuma zedoaria Rosc. volatile oil at dose of 30.6 Î¼l/ml for 14 days and distilled water in control. A 100 Î¼l bacteria were applied on the 7th to 14th day on the gingiva anterior mandibular. At the 15th day, rat was anesthetized then sacrificed. The mandibular gingiva anterior of the rat was taken as histological preparations for HE and immuno-histo chemical staining. CD4+Â  antibody (Santa Cruz Biotechnology, USA) was used for immune staining. Histological preparations were observed under a light microscope.The results showed a strong positive CD4+ expression in the lamina propria and stratum basale of control group while a weak positive expression in lamina propria area of treatment group. From the experiment, it is concluded that the induction of curcuma zedoaria Rosc. volatile oil may reduce gingivitis, indicated by the decrease in CD4+ expression